INTERPERSONAL METAPHOR IN R. S. REGIN SILVEST AND MALINI GANAPATHY’S ANTHOLOGY OF COVID-19 POEMS. - Sri . Rezeki; Amrin . Saragih; Winda . Setyasari (Universitas Negeri Medan, 2022)
This study investigates Interpersonal Metaphor in R.S. Regin Silvest and Malini Ganapathy’s Anthology of Covid-19 Poems. The objectives of the study are (1) to analyze the kinds of interpersonal metaphor applied in R.S. Regin Silvest and Malini Ganapathy’s Anthology of Covid-19 Poems, (2) to describe how the interpersonal metaphor applied in R.S. Regin Silvest and Malini Ganapathy’s Anthology of Covid-19 Poems, (3) and to explain the reason for the realization of interpersonal metaphor in R.S. Regin Silvest and Malini Ganapathy’s Anthology of Covid-19 Poems. This study conducted qualitative research, and as the result of fifty poems there are thirty five Poems of Covid-19 that indicate as Interpersonal Metaphor. Result revealed that there were sixty-three Interpersonal metaphor found in this study namely, Interpersonal metaphor of Mood were thirty-seven and Interpersonal Metaphor of Modality were twenty-six, Interpersonal Metaphor of Mood applied in the Speech Function, namely, Question in Declarative Mood were 18 (49%), Command in Declarative Mood were 13 (35%), Statement in Interrogative Mood were 5 (13%), Question in Imperative Mood 1 (3%), And Interpersonal Metaphor of Modality applied in kinds of modality namely, Modalization were 14 (54%) and Modulation were 12 (46%). From thirty five poems of Covid-19 which consist of Interpersonal Metaphor, there were four meanings and messages found, Expressing the fear of Covid-19 were 15 (43%), Expressing advice and lesson about Covid-19 11 were (31%), Delivering the spirit and positive energy during Covid-19 Pandemic were 5 were (14%) and Expressing hope for better days were 4 (12%).